2012
DOI: 10.18553/jmcp.2012.18.5.375
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Cost Efficacy of Advanced Wound Care Matrices for Venous Ulcers

Abstract: The most expensive AWCM for the treatment of VLUs did not appear to provide the greatest comparative clinical or cost efficacy. Conclusions must be tempered by the small number of available studies (n=3), variability in trial duration (from 12 to 24 weeks) and baseline wound characteristics, and limitations in study quality. Given the high prevalence, economic burden, and substantial disability of VLUs, and the wide variation in costs for AWCMs, payers need more high-quality head-to-head comparisons to guide c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 31 publications
2
54
0
2
Order By: Relevance
“…Similar results were found in a study conducted by Hankin et al [5] who evaluated and compared the clinical and cost efficacy of ECM, HSE, and Talymed as an adjunct to standard care compared with standard care alone for the treatment of chronic VLUs. In this study, investigators considered only product cost and benefit in terms of the number needed to treat.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar results were found in a study conducted by Hankin et al [5] who evaluated and compared the clinical and cost efficacy of ECM, HSE, and Talymed as an adjunct to standard care compared with standard care alone for the treatment of chronic VLUs. In this study, investigators considered only product cost and benefit in terms of the number needed to treat.…”
Section: Discussionsupporting
confidence: 85%
“…Nelzen et al [4] followed patients who had an open VLU for 5 years and found that only 58% had healed, 38% had open unhealed ulcers, and 4% had undergone amputation [4]. VLUs can occur at any age but are more prevalent in the elderly population, with prevalence accentuating with the increase in life expectancy [5]. In the United States, VLUs affect up to 2.5 million patients per year [6] and pose significant clinical and economic challenges to health systems, patients, providers, and the community.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent research has identified improved outcomes for recalcitrant VLUs (>1 year duration or large surface area). 262 No other living cellular therapies have demonstrated benefit for the treatment of VLUs in prospective RCTs. The optimal frequency and timing of reapplication of biologic skin substitutes to VLUs remain controversial with little consensus in published studies.…”
Section: Adjunctive Wound Therapiesmentioning
confidence: 99%
“…Some are reported to contain active growth factors or other attributes that might be beneficial to healing of VLUs. 262 Of the multitude of such products currently marketed, only porcine small intestinal submucosa has prospective RCT data supporting its use to accelerate VLU closure. 263 There is currently not enough information to support the primary use of negative pressure wound therapy for VLUs.…”
Section: Adjunctive Wound Therapiesmentioning
confidence: 99%
“…Apligraf™ is a prefabricated human cell bilayer construct with bovine collagen type 1 and broblasts covered by a strati ed epidermis. Both products are considered advanced wound care matrices for ulcers, but evidence of economic feasibility is questionable (Hankin et al, 2012;.…”
Section: Skin In the Clinicmentioning
confidence: 99%